PENGARUH REVOLUSI SOSIAL TERHADAP KESULTANAN MELAYU DI SUMATERA TIMUR, TAHUN 1946-1947 - Maulimardewa Maulimardewa; Isjoni Isjoni; Kamaruddin Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The eruption of social revolution in East Sumatra can not be separatedfrom the attitude of the sultans, kings and feudal lords in general, were not soenthusiastic about the independence of Indonesia because after Japan entered theJapanese government to revoke all privileges of the nobility and plantation landexpropriated by the workers. The nobility did not feel happy and hope to get their rightsback by working together with the Dutch / NICA, further distanced himself from thepro-republican. Meanwhile, the pro-republican national committee urges the EastSumatra region so special regions like the autonomous governments / kingdomsabolished and replaced it with the people's democratic government in accordance withthe spirit of the struggle for independence. But the pro-repbulik itself split into twocamps; moderates who want a cooperative approach to persuade the nobility and theradicals that prioritizes street violence with the mass mobilization of the workersperkebunan.Hasil this study shows that the social revolution in East Sumatra,destroying what was left of the Republican government in East Sumatra. Officials ofsurvivors preferring locked herself in their house. Like this become the revolutionarymomentum for change in government.Keywords: Social Revolution, East Sumatera